Reproductive Effects of Exposure to Low-Dose Ionizing Radiation: A Long-Term Follow-Up of Immigrant Women Exposed to the Chernobyl Accident - Cwikel, Julie (J Clin Med, 2020)
The Chernobyl accident in 1986 spread ionizing radiation over extensive areas of Belarus and Ukraine, leading to adverse health effects in exposed children. More than 30 years later, exposed children have grown and became parents themselves. This retrospective study from Israel was aimed to evaluate whether Chernobyl-exposed women are at higher risk for adverse reproductive outcomes. Exposed immigrants were identified as high or low exposure based on Caesium-137 soil contamination levels registered in the town they lived in. The exposed group was age matched with three comparison groups: non-exposed immigrant women from the Former Soviet Union (FSU) excluding Belarus and the Ukraine, immigrants from other countries (Non FSU) and Israeli-born women at a ratio of 1:10. Chernobyl-exposed women were more likely to be nulliparous and have fewer children (2.1 + 0.8 vs. 3.1 + 1.8, p < 0.001), were more likely to undergo fertility treatments (8.8% vs. 5.8%, adjusted OR = 1.8, 95%CI 1.04–3.2, p = 0.036), and were also more likely to have anemia after delivery (49.4% vs. 36.6%, OR = 1.7, 95%CI 1.2–2.3, p = 0.001), compared to women in the combined comparison groups. The overall fertility of Chernobyl-exposed women seems to be reduced as reflected by the lower number of children and their greater need for fertility treatments.